The prevalence of dental fluorosis and exposure to fluoride in drinking water: A systematic review - Fatemeh Goodarzi; Amir Hossein Mahvi; Mostafa Hosseini; Saharnaz Nedjat; Ramin Nabizadeh Nodehi; Mohammad Javad Kharazifard; Mina Parvizishad; Zahra Cheraghi (Tabriz University of Medical Sciences, 2016)
Background. Regarding the lack of comprehensive systematic review on the efficacy of water fluoridation and prevalence of dental fluorosis, the aim of the current research was to systematically study the prevalence of dental fluorosis at different levels of water fluoride in the world and lay emphasis on the amount of fluoride in drinking water. Methods. Studies were searched in PubMed, Scopus, SID, and IranMedex, with regard to inclusion criteria. Study validity was assessed with some checklists, and analyses were performed to ascertain the prevalence of dental fluorosis among individuals categorized in age groups. Results. Investigation of the heterogeneity and analysis of the subgroups revealed that in the 6-18 year age group, when water fluoride level was less than 0.7 ppm and there was exposure to water fluoride in the first 6-8 years of life, no significant heterogeneity was detected among the studies in this subgroup. Thus, the pooled estimation of dental fluorosis prevalence in this subgroup was 12.9% (95% CI: 7.5-18.3%). Furthermore, meta-regression indicated that the exposure time to fluoride in drinking water, or exposure to fluoride in supplements, diets, air, etc as well as the quality of studies had a significant relation to the difference in the prevalence of dental fluorosis. Conclusion. The results revealed no heterogeneity in just 2 subgroups, and the results of subgroups could be pooled in them. Furthermore, the number of studies included in this review considerably decreased by considering all the detected confounding factors, whereas other similar systematic reviews mentioned at most 2 factors.